Cryopreservation of Spirulina platensis culture - Tsutsayeva, A. A.; Baliberdina, L. M.; Ananyina, A. E.; Grisha, I. G. (Problems of Cryobiology and Cryomedicine, 2007)
The impact of difference cooling rates on ability to proliferation of Spirulina platensis blue-green algae has been studied. Obtained results have shown that optimal condition of cryopreservation Spirulina platensis culture was rapid cooling by direct plunging into liquid nitrogen of metal container with cell suspension under the protection of cryoprotectant dimethyl sulfoxide in 10% concentration.